TEACHER CHALLENGES IN TEACHING ENGLISH FOR VERY YOUNG LEARNERS AT RA (KINDERGARTEN) RIYADHUL QUR’AN: A PHENOMENOLOGICAL STUDY - Rafidah Fitriana; Sujito (PT. Hasba Edukasi Mandiri, 2026)
This study examines the challenges faced by teacher in teaching English to very young children (TEVYL) in Indonesia, emphasizing the unique characteristics of this age group. To effectively engage young learners, educators must use interactive methods such as games, storytelling, and songs, which align with Vygotsky and Piaget's theories of language acquisition through play and environmental interactions. However, teachers often struggle with choosing the right teaching method, as significant challenges arise, including inadequate training, lack of resources, and classroom density. This research used qualitative research, the number and type of approaches, and the design used a phenomenology, so the researcher describes an individual's life experiences of a phenomenon as described by the teacher as a participant. This study underscores the importance of accommodating a variety of learning styles, visual, auditory, and kinesthetic, to create a multisensory learning environment that suits each child's unique preferences. The research also highlights the urgent need for improved curricula and better teacher training to build teaching effectiveness in early English education. In addition, teachers should foster an atmosphere that supports and encourages self-confidence and participation among very young learners, as their natural tendency to engage and experiment with language is essential for effective learning. The findings suggest a critical need for collaboration between teachers and governments to develop optimal teaching strategies and resources, in order to ensure that early childhood children receive a strong foundation in English language skills during their developmental years.